Kinerja Karyawan: Peran Transformasional Leadership dan Skill Competence - Nur Hikmah (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2020)
Purpose- The aim of this study is to estimate the effect of Transformational Leadership and Expertise Competencies on the employee performance of PBMTI Jepara. Methods- Data were collected through a questionnaire and then analyzed using SmartPLS (Partial Least Square). Findings- The results of the analysis show that transformational leadership and skills competencies influence performance. Unexpectedly, the results show that transformational leadership has a negative effect on performance, while the Skills Competency has a positive effect on performance.